PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PT. CITRA MARGA NUSAPHALA PERSADA Tbk - Mutiara Krisna Wijayanti; Imam Wibowo (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
This research aims to determine the influence of leadership and compensation on employee job satisfaction at PT. Citra Marga Nusaphala Persada, Tbk. Data acquisition using a questionnaire with a differential semantic scale. The sampling technique used is saturated samples. The analysis method uses simultaneousky and partially linear regression. The research results show that both simultaneousky and partially leadership and compensation have a significant influence on the employees job satisfaction of PT. CMNP.